An Analysis of Recurrent Costs of the Free ART Programme of the Government of India - Gupta, Indrani; Trivedi, Mayur; Kandamuthn, Subodh (World Bank, Washington, DC, 2014)
The potential accessibility of Antiretroviral (ARV) drugs at reduced cost and the emergence of largescale Antiretroviral Treatment (ART) programs in other developing countries, have spurred India to launch its own free antivretroviral treatment (ART) program in April 2004. While many countries worldwide have attempted costing of their national program on ART, India did not have any economic or financial estimates of how much it actually costs to run the free ART program, if all sources of spending are included. This study was undertaken with the aim of coming up with preliminary estimates of the recurrent financial cost of the ART program.